Perception of the Peru-China FTA according to company size of Ica's agro-export sector - Perales-Dávila, Nátaly Elizabeth (2023)
This research seeks to determine the relationship between the perception of the development of the avocado agro-export sector in the Ica region according to company size after the Peru-China Free Trade Agreement came into force. The type of study was quantitative, non-experimental, cross-sectional and correlational in scope. The probability sample consisted of 73 avocado producers and agro-exporting companies in the Ica region. A structured questionnaire was applied in three dimensions: productivity, quality and price. The chi-square test was used to test the relationship between the variables. The perception of productivity, quality and price in the avocado agro-export sector and firm size showed a low correlation in each of them. The overall p-value was not less than 0.05 for the chi-square test. Company size is not correlated with the perception of the development of the avocado agro-export sector in the Ica region after the Peru-China FTA.